Obstacles Facing the Handball Tournament in Schools from the Physical Education Teachers’ Perspective at Nablus Province-Palestine - Alaa Yasin; Yuslina Mohamed; Sulaiman Ismail; Qais Yaseen (Usuli Faqih Research Centre PLT., 2025)
Al-Qanatir: International Journal of Islamic Studies Volume: 33 No: 5 (page: 605–620)